2010
DOI: 10.1051/0004-6361/200913138
|View full text |Cite
|
Sign up to set email alerts
|

New rotation periods in the open cluster NGC 1039 (M 34), and a derivation of its gyrochronology age

Abstract: Aims. Employing photometric rotation periods for solar-type stars in NGC 1039 [M 34], a young, nearby open cluster, we use its mass-dependent rotation period distribution to derive the cluster's age in a distance independent way, i.e., the so-called gyrochronology method. Methods. We present an analysis of 55 new rotation periods, using light curves derived from differential photometry, for solar type stars in the open cluster NGC 1039 [M 34]. We also exploit the results of a recently-completed, standardized, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 81 publications
3
46
0
1
Order By: Relevance
“…Here, we also include in our analysis the I-sequence relationships calibrated in Barnes (2007;B07), Mamajek & Hillenbrand (2008;MH08), and Meibom et al (2009;MMS09). We note that we use an updated age-dependence term given by James et al (2010) for the MMS09 relationship.…”
Section: Empirical "I-sequence" Rotation-age Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we also include in our analysis the I-sequence relationships calibrated in Barnes (2007;B07), Mamajek & Hillenbrand (2008;MH08), and Meibom et al (2009;MMS09). We note that we use an updated age-dependence term given by James et al (2010) for the MMS09 relationship.…”
Section: Empirical "I-sequence" Rotation-age Relationshipsmentioning
confidence: 99%
“…A Skumanich-like spin-down is represented with n = 0.5. Other studies have further calibrated the n parameter using open clusters of known ages, and the solar datum -B07: n = 0.5189, MH08: n = 0.566, and MMS09 with the recalibration from James et al (2010): n = 0.5344.…”
Section: Linear Spin-down Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection was made of 189 X-ray sources that are listed in the XMM − Newton Serendipitous Source Catalog (Watson et al 2009). This list of X-ray sources was correlated with lists of M34 cluster members with known rotation periods established by Meibom et al (2011), Irwin et al (2006), and James et al (2010). In total, 41 single stars in the M34 open cluster have been found that have known rotational periods and detected X-ray emissions (Gondoin 2012).…”
Section: X-ray Observations Of the M34 Open Clustermentioning
confidence: 98%
“…NGC 1039(M34)는 나이가 약 2억년 (Meynet et al, 1993;Ianna & Schlemmer, 1993;Jones & Prosser, 1996, 이후 JP96; James et al, 2010)인 중년 산개성단이다. 성간소 광량은 E(B − V ) = 0.07 (Canterna, Perry & Crawford, 1979)이며, 거리지수는 (V − M V ) = 8.60(JP96)이다.…”
Section: 서론unclassified